Imaging features of triple negative breast cancer in a tertiary hospital in South Africa - Bhana-Nathoo, Deepa (My University, 2019)
INTRODUCTION Breast cancer is one of the leading causes of cancer deaths worldwide. Triple negative breast Cancer (TNBC) is an aggressive subtype, commonly described as presenting at a younger age, in women of African descent and in low socioeconomic groups. Commonly it demonstrates benign imaging features making diagnosis a challenge. Early detection and treatment is imperative. AIM To determine the common imaging features of TNBC in South Africa. METHOD A retrospective study was conducted at a tertiary institution in South Africa. the study population included all biopsy proven TNBC patients presenting between 01/01/2012 – 30/06/2016. All the initial mammograms were re-read by three independent radiologists using a data collection sheet. Illegible or incomplete reports were excluded from the study. RESULTS In our population, TNBC commonly presented in African women with an average age of 54.2 and range 25-95 years, with 47% being pre-menopausal. Typical mammographic features were an oval (27%) or irregular (27%) shaped mass with well circumscribed margins (33%). Our lesions were much larger than those reported in the literature (1). Global asymmetry and architectural distortion were commonly associated features. On ultrasound, the lesions were mostly irregularly shaped (56%) with spiculated borders (29%) and hypoechoic (80%) with axillary adenopathy (81%). CONCLUSION The majority of our patient population presented with a clinically palpable mass, that was larger and had more aggressive features than usually described in the literature. This can be attributed to delayed presentation, due to numerous factors. In order to improving the detection rate and reduce mortality, education and screening programs play a major role.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Diagnostic Radiology Johannesburg, 2019
Keywords: Breast--Cancer--treatment; Breast Neoplasms.